Endoscopic ultrasound-guided gallbladder versus bile duct drainage for first-line therapy of malignant biliary obstruction: international multicenter trial - Mangiavillano, Benedetto; Ramai, Daryl; Fugazza, Alessandro; Franchellucci, Gianluca; Spadaccini, Marco; Barbera, Carmelo; Arcidiacono, Paolo Giorgio; De Nucci, Germana; Martínez-Moreno, Belén; Di Mitri, Roberto; Di Matteo, Francesco; Larghi, Alberto; Robles Medranda, Carlos; Anderloni, Andrea; De Luca, Luca; Teoh, Anthony Y. B.; Vargas-Madrigal, Jorge; Forti, Edoardo; Bronswijk, Michiel; Bertani, Helga; Lakhtakia, Sundeep; Do-Cong Pham, Khanh; Crinò, Stefano Francesco; Repici, Alessandro; Facciorusso, Antonio; Biliary Therapeutic EUS Study Group; Vanella, Giuseppe; Frigo, Francesco; Fierro, Giuseppe; Manes, Giampiero; Fuller, Andrew; Ko, Christopher; Morris, John D.; Aparicio, Jose R.; Stigliano, Serena; Arevalo-Mora, Martha; Auriemma, Francesco; Minini, Francesco; Paduano, Danilo; Gentile, Carmine; Fiacca, Matteo; Calabrese, Federica; Alvarado, Victor; Gallo, Camilla; Mutignani, Massimiliano; Van der Merwe, Schalk; Aragona, Giovanni; Mangiafico, Santi; Troncone, Edoardo; Del Vecchio Blanco, Giovanna; Giorgio Mirante, Vincenzo; Ventra, Agostino; Aljahdli, Emad S.; Sundaram, Sridhar; Decembrino, Francesco; Gentile, Marco; Al-Lehibi, Abed; Alfadda, Abdulrahman; Hassan, Cesare (Endoscopy, 2025)
Background Endoscopic ultrasound (EUS)-guided gallbladder drainage (GBD) and EUS-guided choledochoduodenostomy (CDS) with lumen-apposing metal stents are alternative approaches to endoscopic retrograde cholangiopancreatography. We compared EUS-GBD and EUS-CDS as first-line therapies in the management of distal malignant biliary obstruction (MBO).Methods This was an international, multicenter, retrospective, observational study at 28 tertiary care centers from April 2017 to August 2024. Outcomes were compared using propensity score matching. The primary outcome was clinical success. Secondary outcomes included technical success, adverse events, and overall survival.Results 291 patients (mean age 74 [SD 12] years; 130 male) underwent EUS-guided drainage (82 EUS-GBD, 209 EUS-CDS). Most patients developed distal MBO from pancreatic cancer (84 %). After 1-to-1 propensity score matching, 154 patients were selected (77 per group). EUS-GBD and EUS-CDS had similar rates of technical success (96 % [95 %CI 89 %–99 %] vs. 99 % [95 %CI 92 %–99 %]; P = 0.36) and clinical success (86 % [95 %CI 75 %–92 %] vs. 92 % [95 %CI 83 %–97 %]; P = 0.17), respectively. Overall, 11 patients (14.2 % [95 %CI 7 %–24 %]) in each group experienced an adverse event, of which 6 in each group (8 % [95 %CI 2 %–16 %]) were serious.Conclusion Our study showed that in patients with distal MBO, the use of EUS-GBD or EUS-CDS were comparable, with similar rates of efficacy and safety. EUS-GBD could represent an easy and safe option in patients with DMBO without previous cholecystectomy and with clear patency of the cystic duct.